Recurrence and Treatment after Renal Transplantation in Children with FSGS. (24th April 2016) - Kang, Hee Gyung; Ha, Il-Soo; Cheong, Hae Il
Abstract : Focal segmental glomerulosclerosis (FSGS) is a common cause of end-stage renal disease and a common pathologic diagnosis of idiopathic nephrotic syndrome (NS), especially in steroid-resistant cases. FSGS is known to recur after kidney transplantation, frequently followed by graft loss. However, not all patients with FSGS suffer from recurrence after kidney transplantation, and genetic and secondary FSGS have a negligible risk of recurrence. Furthermore, many cases of recurrence achieve remission with the current management of recurrence (intensive plasmapheresis/immunosuppression, including rituximab), and other promising agents are being evaluated. Therefore, a pathologic diagnosis of FSGS itself should not cause postponement of allograft kidney transplantation. For patients with a high risk of recurrence who presented with classical symptoms of NS, that is, severe edema, proteinuria, and hypoalbuminemia, close monitoring of proteinuria is necessary, followed by immediate, intensive treatment for recurrence.